IMPLIKASI TEORI PEMBELAJARAN JEROME BRUNER DALAM NUANSA PENDIDIKAN MODERN - Zulfikar Ali Buto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
Jerome S. Bruner is one of the best-known and influential psychologists of the twentieth century. He was one of the key figures in the so-called ‘cognitive revolution’ - but it is the field of education that his influence has been especially felt. His books The Process of Education and Towards a Theory of Instruction have been widely read and become recognized as classics, and his work on the social studies programme - Man: A Course of Study (MACOS) - in the mid-1960s is a landmark in curriculum development. More recently Bruner has come to be critical of the ‘cognitive revolution’ and has looked to the building of a cultural psychology that takes proper account of the historical and social context of participants. This theory needs to be analyzed which gives some information of cognitive development of the student in teaching learning. Theory not only talks about cognitive but also affective and psychomotor. All of these aspects have been included in teaching learning process, so the teacher have to be responsible to apply these process well. Based on the statement above, the writer is interested to discuss about cognitive concept, applied in teaching-learning process in this era.